TRANSFORMASI DIGITAL DI SEKOLAH NEGERI PESISIR: KAJIAN ASPEK POLITIK, EKONOMI, SOSIAL, DAN BUDAYA PADA IMPLEMENTASI GOOGLE FOR EDUCATION DI SMP NEGERI 1 ANGGANA - Ratnawati, Eny; Kristiyani, Nihan; Warman, Warman; Bahzar, Moh.; Nurlaili, Nurlaili (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the acceleration of digital transformation in education in Indonesia, where platforms such as Google for Education (GfE) have become strategic instruments. However, their implementation in coastal schools often faces non-technical obstacles. Different from general studies, this research focuses on analyzing GfE implementation at SMPN 1 Anggana, a coastal school with ideal technical conditions (internet access, 1:1 Chromebook program), through a political, economic, social, and cultural (PEST) lens. The research used a qualitative case study method with data triangulation through interviews, observations, and document analysis. The results show that although GfE implementation is technically successful, indicated by the widespread use of Google Classroom and a high assignment submission rate (85%), pedagogical optimization remains hampered. Key findings reveal significant challenges in the political (lack of data protection SOPs), economic (the need for a sustainable operational financing model), social (teacher digital competency gap), and cultural (the need to integrate local values). It concludes that technical success does not guarantee complete digital transformation; Strengthened governance, medium-term funding schemes, ongoing teacher training, and contextualized curricula are needed to achieve the full potential of GfE. ABSTRAKPenelitian ini dilatarbelakangi oleh percepatan transformasi digital pendidikan di Indonesia, di mana platform seperti Google for Education (GfE) menjadi instrumen strategis. Namun, implementasinya di sekolah pesisir sering menghadapi kendala non-teknis. Berbeda dari studi umum, penelitian ini berfokus menganalisis implementasi GfE di SMPN 1 Anggana, sekolah pesisir dengan kondisi teknis ideal (internet, program 1:1 Chromebook), melalui lensa politik, ekonomi, sosial, dan budaya (PEST). Penelitian menggunakan metode studi kasus kualitatif dengan triangulasi data melalui wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan bahwa meskipun secara teknis implementasi GfE berjalan baik ditandai dengan penggunaan Google Classroom yang menyeluruh dan tingkat pengumpulan tugas tinggi (85%) optimalisasi pedagogis masih terhambat. Temuan utama mengungkap adanya tantangan signifikan pada aspek politik (ketiadaan SOP perlindungan data), ekonomi (kebutuhan model pembiayaan operasional berkelanjutan), sosial (kesenjangan kompetensi digital guru), dan budaya (perlunya integrasi nilai lokal). Disimpulkan bahwa keberhasilan teknis tidak menjamin transformasi digital yang utuh; diperlukan penguatan tata kelola, skema pendanaan jangka menengah, pelatihan guru berkelanjutan, dan kurikulum kontekstual untuk mencapai potensi penuh GfE.